AB0214 TLR2 ligation induces the production of IL-23/IL-17 via IL-6, STAT3 and NF-KB pathway in patients with primary sjÖgren's syndrome. (23rd January 2014) - Jung, S.M.; Lee, J.H.; Lee, J.; Kim, E.-J.; Kwok, S.-K.; Cho, M.-L.; Park, K.S.; Kim, H.-Y.; Park, S.-H.
Abstract : Background: Sjögren's syndrome is a chronic, slowly progressive autoimmune disease characterized by lymphocytic infiltration of the exocrine glands resulting in dry mouth and dry eyes. Recent studies have suggested that T helper 17 cell (Th17) plays a key role in the pathogenesis of autoimmune diseases, and activation of toll-like receptor (TLR) is thought to be linked with autoimmune inflammation. Objectives: The study was undertaken to investigate the interrelation of TLR and IL-17 in the salivary glands of patients with primary Sjögren's syndrome (pSS) and to determine the role of TLR and IL-17 in the pathophysiology of pSS. Methods: The expressions of various TLRs, IL-17 and the cytokines involved in Th17 cell differentiation including IL-6, IL-23, TNF-αand IL-1βwere examined by immunohistochemistry and confocal staining in salivary glands of pSS patients. After peripheral blood mononuclear cells (PBMCs) were treated with TLR specific ligands, the induction of IL-17 and IL-23 was determined using real-time PCR and ELISA. The signaling pathway that mediates the TLR2 stimulated production of IL-17 and IL-23 was investigated by using treatment with specific signaling inhibitors. Results: TLR2, TLR4, TLR6, IL-17 and the cytokines associated with Th17 were highly expressed in salivary glands of pSS patients but not in controls. The expressions of TLR2, TLR4 and TLR6 were observed in the infiltrating mononuclear cells and ductal epithelial cells, whereas IL-17 and related cytokines were mainly observed in infiltrating CD4+ T cells. The stimulation of TLR2, TLR4 and TLR6 synergistically induced the production of IL-17 and IL-23 from the PBMCs of pSS patients especially in the presence of TLR2 stimulation. IL-6, STAT3 and NF-kB pathways were implicated in the TLR2 stimulated IL-17 and IL-23. Conclusions: Our data demonstrate that TLR2 ligation induces the production of IL-23/IL-17 via IL-6, STAT3 and NF-kB pathway in pSS. Therefore, therapeutic strategies that target TLR/IL-17 pathway might be strong cadidates for treatment modalities of pSS. Disclosure of Interest: None Declared